2000
DOI: 10.1046/j.1440-1754.2000.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection and preterm birth: Evidence of a common causal relationship with bronchopulmonary dysplasia and cerebral palsy

Abstract: Subclinical genital tract infection has been clearly established as a significant cause of spontaneous preterm birth, particularly in early gestations. Bacterial vaginosis organisms rank highly among the pathogens involved in preterm labour and there is considerable beneficial evidence from the use of prophylactic antibiotics for women at high risk of preterm birth. The pathogenesis involves activation of macrophages and the generation of pro-inflammatory cytokines. Bronchopulmonary dysplasia is seen in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
9

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 41 publications
(37 reference statements)
0
29
0
9
Order By: Relevance
“…Many of these works are the epidemiologic studies with great numbers of participants, so the results of the studies are reliable. It was found that abnormalities during pregnancy might give many pathologic consequences for future offspring's life, for example: cardiovascular and cardiopulmonary diseases, including high blood pressure and risk of stroke (1)(2)(3)(4)(5)(23)(24)(25); behavioral, neurological and mental diseases, including cerebral palsy, depression, schizophrenia, epilepsy (24,(26)(27)(28)(29)(30); metabolic diseases, including overweight, type 2 diabetes (2-5,31-33); bronchopulmonary diseases, including asthma (34,35); hearing loss (36). This data show that abnormalities during pregnancy, including obstetric complications and abnormalities of early growth, are associated with or caused by some types of hypoxia.…”
Section: Abnormalities During Pregnancy: Consequences For Future Offsmentioning
confidence: 99%
“…Many of these works are the epidemiologic studies with great numbers of participants, so the results of the studies are reliable. It was found that abnormalities during pregnancy might give many pathologic consequences for future offspring's life, for example: cardiovascular and cardiopulmonary diseases, including high blood pressure and risk of stroke (1)(2)(3)(4)(5)(23)(24)(25); behavioral, neurological and mental diseases, including cerebral palsy, depression, schizophrenia, epilepsy (24,(26)(27)(28)(29)(30); metabolic diseases, including overweight, type 2 diabetes (2-5,31-33); bronchopulmonary diseases, including asthma (34,35); hearing loss (36). This data show that abnormalities during pregnancy, including obstetric complications and abnormalities of early growth, are associated with or caused by some types of hypoxia.…”
Section: Abnormalities During Pregnancy: Consequences For Future Offsmentioning
confidence: 99%
“…1B). Similar analyses with respect to birth weight found the same set of three biomarkers (9,15,17), as well as biomarker 19, correlated with birth weight with p Ͻ 0.02, and biomarker 5 with p ϭ 0.04. None of the globin biomarkers or transthyretin correlated with gestational age or birth weight.…”
Section: Patient Demographicsmentioning
confidence: 62%
“…The reason why some preterm infants of the same gestational age have a mild neonatal course while others go on to develop particular morbidities is of great interest to neonatologists. It has been hypothesized that the release of proinflammatory cytokines such as interleukin (IL)-6, IL-1␤, IL-8, tumor necrosis factor ␣ in amniotic fluid and other body fluids before birth may play a role in several adverse outcomes, including CLD, periventricular leukomalacia (PVL), and cerebral palsy (4,(7)(8)(9).…”
mentioning
confidence: 99%
“…Estos riesgos han sido relacionados con invasión microbiana de la cavidad amnió-tica (IMCA) (3-5) y en menor grado con infección cérvicovaginal (6). Las consecuencias de la infección intrauterina (corioamnionitis clínica, corioamnionitis histológica, funisitis y aumento de citoquinas intraamnióticas) en el niño se asocian con sepsis, bronconeumonía, enterocolitis necrotizante (3-5), con daños neurológicos (leucomalacia periventricular, hemorragia intraventricular, paráli-sis cerebral) y enfermedad crónica pulmonar (7)(8)(9)(10). El pronóstico adverso del neonato se ha correlacionado particularmente con la funisitis, presente en 61% de las embarazadas con IMCA (11).…”
Section: Introductionunclassified